2013
DOI: 10.1590/s0100-204x2013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilaridade genética entre cultivares de mamoneira por meio de marcadores RAPD

Abstract: O objetivo deste trabalho foi identificar cultivares geneticamente divergentes de mamoneira (Ricinus communis) com uso de marcadores RAPD. Um total de 58 iniciadores RAPD foi usado na genotipagem de 15 cultivares. A dissimilaridade genética entre as cultivares foi calculada a partir do índice de Jaccard, tendo-se utilizado o método da média aritmética não ponderada (UPGMA). Foram identificados 552 fragmentos, sendo 311 polimórficos (56,3%). As cultivares foram agrupadas em cinco grupos, evidência de que há div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The implementation of strategies to facilitate the development of castor genotypes with higher oil content and adjusted to different environmental conditions is vital for the castor to be consolidated as an important component of the national program for the production of biodiesel (Machado et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of strategies to facilitate the development of castor genotypes with higher oil content and adjusted to different environmental conditions is vital for the castor to be consolidated as an important component of the national program for the production of biodiesel (Machado et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that only the groups with higher and lower productivity, were formed by the same lineages by any hierarchical agglomerative method used, presenting the longest distance from Mahalanobis (Table 4), which is interesting for the indication of possible crosses between genetically divergent progenitors, leading to the production of hybrid hybrids, however, the lineages with yield of grains between 1400 and 1900, were allocated in different groups depending on the method used, which is not interesting, because it can lead to mistaken decision making (Machado et al, 2013;Rodrigues et al, 2010). The "Euclidean Distance", "Ward Linkage" method, presented a smaller distance between groups 2 and 4, proving that these groups present greater similarity and greater distance between 2 and 3, showing the lowest similarity, which may represent a better result when the selection is in function to a single variable, for example grain yield (Cargnelutti Filho & Guadagnin.…”
Section: For the "Euclidean Distance Completementioning
confidence: 99%
“…Using RAPD markers, together they detected 122 alleles, of which 71 were polymorphic, representing the percentage of polymorphism alleles 58.20%. In the study Machado et al (2013) used 58 RAPD primers for the analysis of 15 castor bean cultivars. The genetic dissimilarity between cultivars was calculated by Jaccard's index, using the unweighted pairgroup method with arithmetic mean (UPGMA).…”
Section: Tablementioning
confidence: 99%